2018
DOI: 10.1166/jnn.2018.15198
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Silica/Polypyrrole Nanocomposites and Application in Corrosion Protection of Carbon Steel

Abstract: Silica/polypyrrole nanocomposites without dopant (SiO2/PPy) and with oxalate dopant (SiO2/PPyOx) were synthesized using polymerization of pyrrole in the presence of nano SiO2. Synthesized SiO2/PPy and SiO2/PPyOx were characterized by FTIR, SEM, TEM and EDX and their electrical conductivities were determined by CV method through the two-point-electrode without electrolyte. The corrosion protection performance of polyvinylbutyral (PVB) coatings containing SiO2/PPyOx was evaluated and compared with that of pure P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 0 publications
0
9
0
4
Order By: Relevance
“…O polipirrol é um polímero condutor que tem sido investigado para inumeras aplicações, destacando-se sensores, baterias, membranas e dispositivos semicondutores. Apresentam algumas vantagens em relação aos semicondutores tradicionais, como a flexibilidade e a facilidade de processamento ( VAN et al, 2018).…”
Section: Polipirrolunclassified
“…O polipirrol é um polímero condutor que tem sido investigado para inumeras aplicações, destacando-se sensores, baterias, membranas e dispositivos semicondutores. Apresentam algumas vantagens em relação aos semicondutores tradicionais, como a flexibilidade e a facilidade de processamento ( VAN et al, 2018).…”
Section: Polipirrolunclassified
“…Among ICPs, polypyrrole (PPy) is widely used due to its unique properties such as environmental stability, high conductivity, and anticorrosion ability [12][13][14][15]. The researches in PPy's applications are focusing on the use of PPy film for a protective coating or anticorrosion additives organic coatings [13,[16][17][18][19][20]. Nanosilica particles are incorporated inside the matrix of conducting polymer in order to form a core-shell structure of ICPs-Silica, which results in the increase of the active area surface of the conducting polymer, compared to its bulk form.…”
Section: Introductionmentioning
confidence: 99%
“…On the whole, there are clear evidences that PPy provides corrosion protection for steel [13][14][15][16][17][18][19][20]. Besides this, several operating corrosion protection mechanisms have been proposed, such as barrier protection, corrosion inhibition, and anodic protection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All in all, it is believed that PPy provides corrosion protection for steel [12][13], however to completely understand about the mechanism is still challenging because of different possible oxidation states and experimental parameters. It has been suggested that PPy can reduce the rate corrosion by forming a protective barrier layer and anodic protection, occurring a shift in corrosion potential to more positive values [14].…”
Section: Introductionmentioning
confidence: 99%